2016
DOI: 10.1111/trf.13887
|View full text |Cite
|
Sign up to set email alerts
|

Blood products use in France: a nationwide cross‐sectional survey

Abstract: Except for insufficient FFP dosing per patient and limitations on assessment of indications for prescribing, transfusion practices were in agreement with national guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…De Francisci 2004 was the only trial including participants with other diagnoses (adults requiring a liver transplant and children requiring cardiac surgery). Although individuals with haemato-oncological malignancies represent a large proportion of people receiving platelet transfusions, we cannot extrapolate these finding to individuals with other diagnoses (Charlton 2014; Fedele 2016; Fillet 2016; Jones 2013).…”
Section: Discussionmentioning
confidence: 99%
“…De Francisci 2004 was the only trial including participants with other diagnoses (adults requiring a liver transplant and children requiring cardiac surgery). Although individuals with haemato-oncological malignancies represent a large proportion of people receiving platelet transfusions, we cannot extrapolate these finding to individuals with other diagnoses (Charlton 2014; Fedele 2016; Fillet 2016; Jones 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Small studies of a few institutions in both the U.S. and internationally have evaluated transfusions in hospitalized patients . Roubinian et al examined in‐hospital determinants of RBC transfusions using the Kaiser Permanente Health system database using data from 21 hospitals over a four‐year period (2008–2011).…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies demonstrated overtransfusion and administration of double units as common errors [3,4]. Moreover, despite international guidelines are very clear about a sufficient dosage of plasma, underdosage of plasma seems to be an international phenomenon [4,5]. The reason for these observations remains unclear.…”
Section: Introductionmentioning
confidence: 74%